(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Mastopathy is the most common disease in women, accounting for 90% of the flow of diseases in mammology. The etiology of fibrocystic mastopathy has not been fully elucidated, but many studied risk factors include endocrine disorders, particularly insulin resistance and thyroid disease.